Studi Komparasi Prestasi Belajar Siswa Santri dan Non Santri pada Mata Pelajaran Fiqih di Kelas X Madrasah Aliyah Hidayatul Mubtadiin Sidoharjo Jati Agung Lampung Selatan Tahun Pelajaran 2024/2025: Penelitian - Yulia Nur Kholifah; Sarpendi; Ami Latifah (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The differences in learning environments between boarding (santri) and non-boarding (non-santri) students raise questions about their impact on academic achievement, particularly in the subject of Fiqh. This study aims to address this issue using a quantitative approach with a comparative method. The research sample consisted of 20 students from Madrasah Aliyah Hidayatul Mubtadiin Jati Agung, divided into two groups: 10 santri students who live in the dormitory and 10 non-santri students who live outside the dormitory. Data were collected through documentation of Fiqh subject scores and analyzed using the Independent Sample T-Test with the assistance of IBM SPSS Statistics 2023 software. The analysis results showed a statistically significant difference between the two groups. The average score of santri students was 74.00, which was higher than that of non-santri students, who had an average score of 51.60, with a significance level of p = 0.000 (p < 0.05). These findings indicate that dormitory life, which is rich in religious guidance and discipline, positively contributes to the academic performance of santri students. The implications of these results encourage the need to strengthen the mentoring system for non-santri students to provide them with a similar learning experience.